1993
DOI: 10.1007/bf00199761
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-trisphosphate as fertilization signal in plants: testcase Chlamydomonas eugametos

Abstract: Abstract. Within the first 2 h of sexual reproduction, gametes of the green alga Chlamydomonas eugametos agglutinate, fuse via their mating structures, de-agglutinate and swim off as vis-fi-vis pairs. During this period, increases in intracellular inositol 1,4,5-trisphosphate levels and changes in polyphosphoinositide synthesis were associated with cell fusion. The protein-kinase-C inhibitor staurosporine (0.1-0.2 gM) inhibited the de-agglutination of pairs and therefore prevented them swimming away, while ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…PLD activity was first demonstrated in plants (Hanahan and Chaikoff, 1947), but although it has been associated with a number of plant processes, no one has shown that it is involved in cell signaling (for reviews, see Heller, 1978;Wang, 1993). A good plant system for studying its possible involvement is the biflagellate green alga Chlamydomonas spp, because there is already convincing evidence for the presence of PLC signaling activity (Irvine et al, 1989Schuring et al, 1990;Brederoo et al, 1991;Dr$bak, 1992Dr$bak, , 1993Musgrave et al, 1992Musgrave et al, ,1993Quarmby et al, 1992;Yueh and Crain, 1993;Cote and Crain, 1994;Munnik et al, 1994aMunnik et al, , 1994bQuarmby and Hartzell, 1994). What is more, this pathway is activated by G protein activators with dramatic effects for gametes; for example, they deflagellate and activate their mating structures, which are two well-established Ca2+ responses (Schuring et al, 1990;Musgrave et al, 1992;Quarmby et al, 1992;Quarmby, 1994;Quarmby and Hartzell, 1994;Sanders and Salisbury, 1994).…”
Section: Mastoparan-stimulated Formation Of Ptdohmentioning
confidence: 99%
“…PLD activity was first demonstrated in plants (Hanahan and Chaikoff, 1947), but although it has been associated with a number of plant processes, no one has shown that it is involved in cell signaling (for reviews, see Heller, 1978;Wang, 1993). A good plant system for studying its possible involvement is the biflagellate green alga Chlamydomonas spp, because there is already convincing evidence for the presence of PLC signaling activity (Irvine et al, 1989Schuring et al, 1990;Brederoo et al, 1991;Dr$bak, 1992Dr$bak, , 1993Musgrave et al, 1992Musgrave et al, ,1993Quarmby et al, 1992;Yueh and Crain, 1993;Cote and Crain, 1994;Munnik et al, 1994aMunnik et al, , 1994bQuarmby and Hartzell, 1994). What is more, this pathway is activated by G protein activators with dramatic effects for gametes; for example, they deflagellate and activate their mating structures, which are two well-established Ca2+ responses (Schuring et al, 1990;Musgrave et al, 1992;Quarmby et al, 1992;Quarmby, 1994;Quarmby and Hartzell, 1994;Sanders and Salisbury, 1994).…”
Section: Mastoparan-stimulated Formation Of Ptdohmentioning
confidence: 99%
“…Chlamydomonas cells are able to increase the cytoplasmic concentration of calcium either via rhodopsinactivated channels in the cell body, voltage-gated channels on the¯agella (Hartz and Hegemann 1991;Beck and Uhl 1994) or by activating phospholipase C which hydrolyses phosphatidylinositol 4,5-bisphosphate into diacylglycerol (DAG) and inositol-1,4,5-trisphosphate (InsP 3 ; Musgrave et al 1992Musgrave et al , 1993Quarmby and Hartzell 1994). The InsP 3 can then induce the release of calcium from internal stores by binding to the InsP 3 receptor (Berridge 1993).…”
Section: Introductionmentioning
confidence: 99%
“…These minor phospholipids are important precursors for inositol 1,4,5-triphosphate and diacylglycerol, which could mediate the formation of the Ca 2+ /cAMP signal transduction system needed for successful mating and zygote development (Schuring et al, 1990;Goodenough et al, 1993;Musgrave et al, 1993;Kuin et al, 2000). Notably, PtdIns(4,5)P 2 becomes enriched at the shmoo tip in the mating reaction of yeast.…”
Section: Discussionmentioning
confidence: 99%